Effect of Cost-Related Medication Non-adherence Among Older Adults With Medication Therapy Management - Zhang, Weiwei; Lv, Gang; Xiong, Xiaomo; Li, Minghui (Frontiers in Medicine, 2021)
ABSTRACT Background: Medication therapy management (MTM) was established by the Center for Medicare and Medicaid Services (CMS) with the aim to improve medication adherence. However, the national prevalence of cost-related medication non-adherence (CRN) is still unknown and there is a literature gap in the association between MTM services and CRN. Methods: A cross-sectional study was conducted. A nationally representative study sample from Medicare Current Beneficiary Surveys (MCBS) was used. Survey sampling weights were applied for national estimates of CRN. Weighted multivariable logistic regressions controlling for covariates were conducted to investigate the effect of the MTM on the CRN. Results: The study identified 1,549 MTM-eligible beneficiaries. The prevalence of CRN was higher in MTM-eligible individuals than in non-MTM eligible individuals (24.14% vs. 13.44%; P < 0.001). According to the results of multivariable logistic regressions, we found that MTM eligibility was significantly associated with a higher prevalence of CRN (OR: 1.59; 95% CI: 1.28-1.96). Additionally, some other variables such as health status, with or without low-income subsidy are also associated with CRN. Conclusions: Our findings suggest that the prevalence of CRN in MTM-eligible beneficiaries was higher than in non-MTM eligible beneficiaries. Further studies with the longitudinal design are warranted to clarify the relationship between MTM and CRN. Alternative strategies to improve CRN should be considered in future Medicare Part D Enhanced MTM Models.